2005
DOI: 10.1109/tap.2005.858863
|View full text |Cite
|
Sign up to set email alerts
|

Radiation properties of one-dimensional random-like antenna arrays based on Rudin-Shapiro sequences

Abstract: The development of exotic new materials, such as metamaterials, has created strong interest within the electromagnetics (EM) community for possible new phenomenologies and device applications, with particular attention to periodicity-induced phenomena, such as photonic bandgaps (PBG). Within this context, motivated by the fairly recent discovery in X-ray crystallography of "quasicrystals," whose diffraction patterns display unusual characteristics that are associated with "aperiodic order," we have undertaken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…More recently, RS sequences have found important practical applications as signal processing tools for spreading spectrum communication and encryption systems [11,12]. One of the first applications of RS sequence and polynomials in electromagnetics was in [13] where the time-harmonic radiation properties of 1-D RS-based antenna array configurations have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, RS sequences have found important practical applications as signal processing tools for spreading spectrum communication and encryption systems [11,12]. One of the first applications of RS sequence and polynomials in electromagnetics was in [13] where the time-harmonic radiation properties of 1-D RS-based antenna array configurations have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…These investigations, pioneered by Bombieri and Taylor [5], have demonstrated intriguing connections between diffraction physics and number theory (algebraic integers, prime numbers). Within this context, for the two-letter substitution rules of interest here, a key role is played by the so-called substitution matrix r[ s] (4) which describes the symbol distribution in (3) [5][6][7]. It can be shown that, for the case of primitive substitution rules, the substitution matrix in (4) admits two real eigenvalues Al and A2, with Al> 1A21 [6].…”
Section: Summary Of Relevant Theoretical Resultsmentioning
confidence: 99%
“…* The discrete (Bragg-type) spectrum generally depends on the eigenvalues of the substitution matrix in (4), and on the scale ratio d. Idb It is interesting to note that the substitution matrix depends only on the number of letters in the substitution rules, and not on their ordering. For rational values of the scale ratio, there exist also "trivial" Bragg-type modes whose wavenumbers do not depend on the substitution rules.…”
Section: Summary Of Relevant Theoretical Resultsmentioning
confidence: 99%
See 2 more Smart Citations